The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/brainsci12060704
|View full text |Cite
|
Sign up to set email alerts
|

Music-Enhanced Emotion Identification of Facial Emotions in Autistic Spectrum Disorder Children: A Pilot EEG Study

Abstract: The Autistic Spectrum Disorder (ASD) is characterized by a difficulty in expressing and interpreting others’ emotions. In particular, people with ASD have difficulties when interpreting emotions encoded in facial expressions. In the past, music interventions have been shown to improve autistic individuals’ emotional and social skills. The present study describes a pilot study to explore the usefulness of music as a tool for improving autistic children’s emotion recognition in facial expressions. Twenty-five ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Thompson et al reported that ASD children have difficulty looking at people, particularly their faces, but when they watched videos of someone singing or reading a story, they would look more at the person if they were singing and if the story was familiar to them; thus, using songs and familiar stories may be a way to help children with autism to naturally engage with others ( 25 ). Similar studies have shown that music can be used to improve emotion recognition in facial expressions and emotion induction through facial stimulation in children with high functioning ASDs ( 26 ).…”
Section: Discussionmentioning
confidence: 85%
“…Thompson et al reported that ASD children have difficulty looking at people, particularly their faces, but when they watched videos of someone singing or reading a story, they would look more at the person if they were singing and if the story was familiar to them; thus, using songs and familiar stories may be a way to help children with autism to naturally engage with others ( 25 ). Similar studies have shown that music can be used to improve emotion recognition in facial expressions and emotion induction through facial stimulation in children with high functioning ASDs ( 26 ).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, of the 54 music therapy studies, 85% (46) focus on children with ASD [ 13 , 23 , 26 , 27 , 29 , 33 , 34 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 52 , 53 , 54 , 58 , 60 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 79 , 83 , 84 , 85 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ], 11.3% (6) focus on children with ADHD [ 22 , 41 , 42 , 52 , 72 , 82 , 94 ], and 3.7% (2) focus on children with language disorders [ 14 , 15 , 16 , 17 , 18 , ...…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, of the 54 music therapy studies, 85% (46) focus on children with ASD [13,23,26,27,29,[33][34][35][39][40][41][42][43][44][46][47][48][52][53][54]58,60,66,[68][69][70][71][72][73][74][75][76]79,[83][84][85][88][89][90][91][92][93][94], 11.3% (6) focus on children with ADHD [22,41,42,52,72,82,94], and 3.7% (2) focus on children with language disorders .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research on using music as an intervention for ASD has centred in communication behaviours [25], but other more recent approaches have been proposed. For instance, Ramirez et al [26] explore the potential usefulness of music as a tool for improving ASD children's emotion recognition in facial expressions. By exposing children with ASD to facial expressions with different emotions with and without emotion-matching background music, emotion identification improvement was measured both in terms of verbal response accuracy (perceived emotion), and brain (EEG) activity response (induced emotion).…”
Section: Opinionmentioning
confidence: 99%